Age-specific serum anti-Müllerian hormone levels: estimates from a large population-based sample. (October 2014) - Tehrani, F. R.; Mansournia, M. A.; Solaymani-Dodaran, M.; Azizi, F.
Abstract Objective Despite the wide use of anti-Müllerian hormone (AMH) measurement as a clinical marker for assessment of ovarian reserve, a population-based estimate for its reference values is not available. In this study, we have estimated age-specific AMH levels in a large sample of fertile women directly selected from a general population cohort. Methods All women who were naturally fertile and aged 18–50 years with regular menstrual cycles were selected from the Tehran Lipid and Glucose Study cohort and their blood levels of AMH were measured. Centiles for AMH distribution were estimated according to the exponential–normal 3-parameter model. We repeated the analysis after including a subgroup of women aged 40–50 years who met all the eligibility criteria except having entered natural menopause after age 40 years (n = 141). Results A total of 1015 women entered the study. The mean age was 36.7 years (standard deviation 7.5 years) and the mean body mass index was 27.0 kg/m2 (standard deviation 4.6 kg/m2). A non-linear decline of serum AMH concentration with age was observed. Age-specific AMH levels for the 5th, 10th, 25th, 50th, 75th, 90th and 95th percentiles were calculated. Results were reproduced after inclusion of 141 women aged 40–50 years who met all the eligibility criteria except having entered natural menopause after 40 years. Conclusion In this study, we have presented a nomogram of age-specific estimates of anti-Müllerian hormone in a large sample of naturally fertile women within the general population. This could help clinicians in more accurate individual interpretation of serum AMH levels in healthy women.